MODEL OPTIMASI PELAYANAN NASABAH BERDASARKAN METODE ANTRIAN (QUEUING SYSTEM) - Irmayanti Hasan (University of Merdeka Malang, 2011)
Customer queuing is a common phenomenon that often happens in getting services. In an attempt to get theservice from the tellers, customers often judge the quality of bank operation system based waiting time periodor teller speed in providing services to the customers. The Islamic banks in Malang is developing rapidly, oneof the banks is PT. Bank Mega Syariah Malang needs optimization analysis of queueing system to ensurecustomers satisfactions. The bank should be able to provide the best service by providing fast service tocustomers and avoid too long waiting time. The calculation results show that customer arrival pattern is 1minute 51 seconds. As for the service pattern is 4 minutes 42 seconds. The queuing system application in PT.Bank Mega Syariah Malang is good because the teller average service time is 4 minutes 42 seconds teller andteller standard time is 3 minutes 39 seconds which the average time is smaller than the expected by thecustomer that is 5 minutes. Besides that the average time of customers wait in a queue system and total system(queuing and service facilities) is less than 1 minute 32.09 seconds.